Energy Sources and Carbon Emissions in the Iron and Steel Industry Sector in South Asia - Sarker, Tapan; Corradetti, Roberto; Zahan, Muslima (International Journal of Energy Economics and Policy, 2012)
This paper examines CO2 emissions from electricity and fuel consumption of different energy sources consumed in the Iron and Steel Industry sector (non-ferrous included, also known as basic metal) in five South Asian countries including Bangladesh, India, Nepal, Sri Lanka and Pakistan. The study finds that about 30% of the total energy in the manufacturing industry is used in this sector, which is about 11% of total industrial input, contributing approximately 13% to the Manufacturing Value Added (MVA). Electricity, on the other hand, shares almost 60% of total energy consumption in the five countries in South Asia, followed by natural gas, coal, kerosene and diesel. The study also finds that CO2 emissions vary across sectors in countries in which the study was conducted. For instance, while in Bangladesh CO2 emissions are primarily caused by electricity generation, in India the majority of CO2 emissions are originated from coal. On the contrary, CO2 emissions in Nepal are mostly generated through other fuels such as Charcoal, Diesel and Kerosene. This study provides some policy recommendations, which could help reduce CO2 emissions in the Iron and Steel Industry sector in the South Asian region. Keywords: CO2 Emissions, Iron & Steel Industry, South Asia JEL Classifications: L61; Q40; Q51